Techno-economic Analysis of New Wind Power Plant Development in Southern Sulawesi Electrical Power System - Santosh (Syntax Corporation, 2023)
Global warming due to carbon emissions has resulted in climate change, which negatively impacts the lives of living things. On the other hand, electricity demand is increasing every year due to the increasing human population, economic growth and equipment electrification. At the moment, most of the electricity generation in Indonesia uses fossil energy power plants which produce carbon emissions. PT. PLN (Persero) is a State-Owned Enterprise tasked with managing the electricity system in Indonesia. PT. PLN (Persero) through the General Plan for Electricity Supply (RUPTL) for 2021-2030 is targeting the construction of New and Renewable Energy Power Plants. One of possible plan is the Wind Power Plant (WPP) construction in the Southern Sulawesi electrical power system. The use of WPP is expected to reduce carbon emissions. However, the integration of WPP causes other problems in the existing system such as dropped voltage, increased equipment loading, increased short circuit current and decreased stability. So, it is necessary to conduct a study on the effects of integrating WPP into the existing system. Using DIgSILENT Power Factory software, Load Flow, Short Circuit and Transient Stability simulations were carried out. Then an economic analysis was carried out including calculating net present value (NPV), internal rate of return (IRR), profitability index (PI), payback period (PBP) and levelized cost of energy (LCOE. The use of WPP at a certain capacity will not disrupt the stability of the system's power because it is still supported by the fast response generators in the system during variable WPP output. Also voltage drop, equipment loading and short circuit current will not exceed the design value of the system. From financial aspect, with certain assumptions, WPP development can be proven to be economically feasible.